If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -6x = 140 Solving 17 + -6x = 140 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -6x = 140 + -17 Combine like terms: 17 + -17 = 0 0 + -6x = 140 + -17 -6x = 140 + -17 Combine like terms: 140 + -17 = 123 -6x = 123 Divide each side by '-6'. x = -20.5 Simplifying x = -20.5
| 13p-4=106 | | .75k-6=0.25k+1 | | 9-8y=33 | | 19x^2-95x-456=0 | | 17p-21=87 | | Y+40= | | x^2+7x=-17 | | 3(5x+5)=6(x+4) | | 3(2x-4)=9(x-3) | | 8x-3-(-3-13)=-6-(y+-3) | | 2x-3(4)=0 | | 12x-16=5x+40 | | 37-7=12 | | (3x+5)(x+2)(x-1)=0 | | 9(y-6)=18 | | f(x)=-x^4+8x^2-16 | | 303-0.003= | | 0.003-303= | | 6q^2-2q=5q^2-4q+63 | | -29=9-5x | | 0.003-3.03= | | v/3-8=-6 | | 2x+2(5+x)=10 | | 54=7u-9 | | 13/5=x/5 | | 27=9(v-6) | | 0=8c | | -6-x=y | | (2x+3)(x^2+x-2)=0 | | 91x=7 | | -4=8h-4 | | 24x^2-96x-504=0 |